VD_FINDINFO Arrêt / 2025 / 876 vom 5. November 2025 - VD Tribunal cantonal (2025)
LOI FÉDÉRALE SUR L'ASSURANCE-INVALIDITÉ, IMPOTENCE, NOUVELLE DEMANDE | 42 LAI, 9 LPGA, 37 RAI, 38 RAI, 87 al. 2 RAI, 87 al. 3 RAI